2022
DOI: 10.1111/jfbc.14455
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of root from Arctium lappa L ameliorates obesity and hepatic steatosis in rats by regulating the AMPK / ACC / CPT ‐1 pathway

Abstract: Burdock (Arctium lappa L) root is eaten as a vegetable in many countries and used as an ethnomedicine because of its various pharmacological effects. The objective of this study was to investigate the underlying mechanisms of ethanolic extract of root from Arctium lappa L root (ALE) to lose weight and regulate lipid metabolism. The results showed that ALE can regulate lipid metabolism level and inhibit the weight gain of rats induced by the high‐sugar and high‐fat diet. The contents of triglyceride and cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…This indicates that chlorogenic acid inhibited hepatic cell injury induced by oleic acid. Therefore, this result is consistent with burdock roots protecting hepatic cells against hepatic steatosis from the damage induced by lipotoxicity [8], which also indicates that chlorogenic acid is a critical functional factor in the treatment of metabolic fatty liver disease.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This indicates that chlorogenic acid inhibited hepatic cell injury induced by oleic acid. Therefore, this result is consistent with burdock roots protecting hepatic cells against hepatic steatosis from the damage induced by lipotoxicity [8], which also indicates that chlorogenic acid is a critical functional factor in the treatment of metabolic fatty liver disease.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, 3-hydroxy-3-methyl glutaryl coenzyme A reductase (HMG-CoR), glycerol-3-phosphate acyltransferases (GPAT) and sterol regulatory element-binding protein 1 (SREGBP-1) are related to lipid synthesis; hormone-sensitive lipase (HSL) promotes lipolysis; and acetyl-CoA carboxylase (ACC) and carnitine palmitoyltransferase-1 (CPT-1) are related to fatty acid β-oxidation, which are all regulated by AMPK. Our previous study also found that ethanol extract from burdock root can enhance the ability of fatty acid β-oxidation in the liver of obese rats by phosphorylating AMPK [8]. At the same time, AMPK is regulated by the second messenger such as cAMP and calcium/calmodulin-dependent protein kinase beta (Ca 2+ /CaMKK 2 ); chlorogenic acid may affect the signaling pathway associated with the second messenger.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, CPT‐1, a key regulator of fatty acid oxidation, is closely linked to the process of fatty acid oxidation (Liu et al., 2011 ). AMPK activation also upregulates PPARα and its downstream targets, including CPT‐1, thereby promoting fatty acid oxidation (Diniz et al., 2021 ; Ma et al., 2022 ). In our study, we observed elevated phosphorylation levels of AMPK and changes in the expression of its downstream molecules, including SREBP‐1c, PPARα, CPT‐1, and FAS, following HP treatment in HCD‐fed NAFLD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Among several officinal plants, Burdock ( Arctium lappa L.), Dandelion ( Taraxacum officinale ), and Lemon balm (Melissa officinalis ) have been used for their edible and medicinal properties [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%